![](https://blog.hocmai.vn/wp-content/uploads/2017/07/hot.gif)
![](https://blog.hocmai.vn/wp-content/uploads/2017/07/hot.gif)
a)[tex](2x-1)^{3}= -8[/tex]
b)[tex]3^{-1}.4^{x}+3.4^{x}=\frac{5}{3}.2^{7}[/tex]
c)[tex]3^{4-x}=27[/tex]
d)[tex](3x+1,5)^{1000}+(2,7-y)=0[/tex]
e)[tex](y^{2}+1)^{2}= 25[/tex]
f)[tex](5x-2)^{20}=(5x-2)^{16}[/tex]
b)[tex]3^{-1}.4^{x}+3.4^{x}=\frac{5}{3}.2^{7}[/tex]
c)[tex]3^{4-x}=27[/tex]
d)[tex](3x+1,5)^{1000}+(2,7-y)=0[/tex]
e)[tex](y^{2}+1)^{2}= 25[/tex]
f)[tex](5x-2)^{20}=(5x-2)^{16}[/tex]